Fasting and Dietary Restriction Impact on Immune System in Aging Population: A Narrative Review - Handayani, Luh Gede Laksmi Rahayu; Rahmawati, Fitriana Nur; Saputri, Dianita Susilo (Writing Center IMERI FMUI, 2023)
Dietary habits and nutrition metabolism are strongly associated with human physiology. Overnutrition or calorie excess has been shown to have many deleterious effects. At the same time, the impact of fasting as part of dietary restriction (DR) remains elusive, especially on the immune system during the aging process. Here, we describe current updates of fasting and DR impact on the immune system and host responses in the aging population. Generally, fasting causes alteration in immune cell distribution by increasing the homing of peripheral cells to the bone marrow. In the aging population, fasting reduces the inflammatory response and promotes cell regeneration. Additionally, fasting is associated with the B cell clonal expansions important to counter infection. This review offers new perspectives and enhances our understanding of immunosenescence as a key to healthy aging.